2013
DOI: 10.3109/0886022x.2013.832314
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C, creatinine, estimated glomerular filtration, and long-term mortality in stroke patients

Abstract: Renal dysfunction is associated with mortality in patients after ischemic stroke. Cystatin C is a potentially superior marker of renal function compared to creatinine and estimated glomerular filtration rate (GFR). In our observational cohort study, 390 Caucasian patients suffered from acute ischemic stroke (mean age 70.9 years; 183 women and 207 men) were included and prospectively followed up to maximal 56 months. Serum creatinine and cystatin C were measured at admission to the hospital; GFR was estimated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
1
13
1
Order By: Relevance
“…A more extensive investigation in the future on this particular issue will be of importance. In addition, we realize that our finding is inconsistent with other studies describing the “U”- or “J”-shaped association 12 , 14 ) . This may be due to inevitable differences in study population, eGFR equations, or study design.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A more extensive investigation in the future on this particular issue will be of importance. In addition, we realize that our finding is inconsistent with other studies describing the “U”- or “J”-shaped association 12 , 14 ) . This may be due to inevitable differences in study population, eGFR equations, or study design.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite growing interest in similar subject, divulging the association either in overall stroke 7 9 ) , ischemic 10 14 ) or hemorrhagic subtypes 15 17 ) , in-between study findings have been contradictory, for example, while Yahalom et al 9 ) and Tsagalis et al 7 ) showed significant and positive result between low eGFR and mortality and poor outcome after stroke, the opposite was reported by Yang et al 8 ) . Result interpretations were complicated by small sample size 7 9 , 12 15 , 17 ) , non-population-based setting 7 9 , 11 , 12 , 14 ) , narrow-range eGFR category 7 , 11 , 13 15 ) , or lack of control for stroke severity 12 , 15 ) . The present study deals with these issues by employing data from a large-scale population-based setting registry, implementing wide-range eGFR category, and separating analyses between non-RRT and RRT patients.…”
Section: Discussionmentioning
confidence: 94%
“…Many biomarkers have been shown to be associated with the prognosis of cerebral infarction, such as hemoglobin, albumin, total bilirubin, fasting blood glucose, creatinine, uric acid,prealbumin etc. [12,13,[33][34][35][36][37][38]. These biomarkers were analyzed comprehensively by logistic regression in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking status was assessed with serum cotinine levels. Socioeconomic status was defined by using the poverty income ratio as a categorical variable with five categories: [0,1], (1,2], (2,3], (3,4], and (4,5]. The reference group is poverty income ratio of one or less (ie, below the poverty line).…”
Section: Discussionmentioning
confidence: 99%
“…Most association studies consider linearity or non-linearity separately without quantitatively assessing which of the models better describes the relationship between a given physiological indicator and all-cause mortality. 5 , 6 A few studies have compared the prediction performance of various types of model such as linear, quadratic, cubic, and logarithmic but have not validated their findings, leading to model overfitting and lack of generalisation to other populations or cohorts. 7 Model flexibility has also led to the so-called vibration of effects, 8 whereby the direction of associations is a function of how variables are modelled, which is a threat to both generalisability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%